Edukasi Bahaya Konsumsi Rokok pada Anak di Bawah Umur - ENNI SARI SIREGAR (XXXXX, 2023)
Children and teenager are the pioneer of the next generation and must be prepared since early stage to become individuals who are able to fulfil these expectations, of course to be intelligent children both psychologically and physically. One of the crucial problems is the large number of underage children who become active smokers, this is very detrimental because the effects caused by smoking can endanger children's health and can even threaten the child's future. This activity held in Kampung Dalam Lingkungan I Pasar Gunung Tua. The communication model used is the AIDDA model (Awareness, Interest, Desire, Decision, and Action). The results of the implementation of this activity in general can be said to have received full enthusiasm from the participants who in this activity were children, youth and parents. From three of the posters attached to shop two were still attached and five of the seven posters distributed to participants were still well kept by the participants.This shows that participants feel that information about the dangers of smoking is important to increase knowledge and ultimately be able to make decisions and even take action to stop smoking or at least reduce the amount of cigarette consumption